2018
DOI: 10.1016/j.bbamcr.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-independent role of nuclear RIPK1 in regulating parthanatos through physical interaction with PARP1 upon oxidative stress

Abstract: Regulated necrosis occurs in various pathophysiological conditions under oxidative stress. Here, we report that receptor-interacting protein kinase 1 (RIPK1), a key player in one type of regulated necrosis (necroptosis), also participates in another type of poly (ADP-ribose) polymerase 1 (PARP1)-dependent regulated necrosis (parthanatos). Various biological signatures of parthanatos were significantly attenuated in Ripk1 mouse embryonic fibroblasts, including PARylation, nuclear translocation of apoptosis-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…OS has been reported to play an essential role in IRI . Among the predicted miRNAs regulating the RIPK1 gene, only miR‐590‐3p had the potential of suppressing OS, and RIPK1 gene was found to be associated with OS . Thus, a hypothesis was made that miR‐590‐3p could influence IRI by regulating RIPK1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…OS has been reported to play an essential role in IRI . Among the predicted miRNAs regulating the RIPK1 gene, only miR‐590‐3p had the potential of suppressing OS, and RIPK1 gene was found to be associated with OS . Thus, a hypothesis was made that miR‐590‐3p could influence IRI by regulating RIPK1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, PSPC significantly restored the NAD + level in the livers of HFD-treated mouse. Oxidative stress is widely reported to be responsible for NAD + depletion by impairing NAD + biosynthesis and elevating NAD + breakdown under various pathological conditions including metabolic syndrome (51,52). Consistent with our previous works (17)(18)(19), our present results showed that PSPC markedly abated HFD-induced oxidative stress in mouse livers.…”
Section: Discussionsupporting
confidence: 93%
“…In order to elucidate the specific molecular pathways required for ZBP1-induced apoptosis in the context of VZV infection, we sought to determine whether RIPK3 was necessary for cell death. To this end, we performed infectious centre assays with ARPE-19 cells, a cell line known to be permissive to VZV infection that possesses a full complement of caspases but does not express RIPK3 (57). For this assay, only the VZV parent strain and the VZV-RHIMmut were compared, since we had established that the IQIG core tetrad is crucial for the prevention of ZBP1-induced cell death.…”
Section: Resultsmentioning
confidence: 99%